THE DEVELOPMENT WITH MINIMUM MATERIAL FOR AN AESTHETIC ROTATION SURFACE - Liliana LUCA; Minodora Maria PASĂRE; Cătălina IANĂȘI (Fiabilitate şi Durabilitate)
In this paper we present the rotation surface obtained by the rotation by the vertical ax of a curved line formed of two equals circle arches. The rotation surface presented in the paper may present interest for the manufacturing of different objects. The approximate development of the rotation surfaces proposed in this paper are based on classic method of descriptive geometry. In the paper are presented two variants for drawing the development surface: the first version with 12 elements and the second version with 24 elements. The second option for the development has the advantage that it uses much less material.